2014
DOI: 10.1007/s00221-014-4087-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrifying the motor engram: effects of tDCS on motor learning and control

Abstract: Learning to control our movements accompanies neuroplasticity of motor areas of the brain. The mechanisms of neuroplasticity are diverse and produce what is referred to as the motor engram, i.e. the neural trace of the motor memory. Transcranial direct current stimulation (tDCS) alters the neural and behavioral correlates of motor learning, but its precise influence on the motor engram is unknown. In this review, we summarize the effects of tDCS on neural activity and suggest a few key principles: 1) firing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 255 publications
(365 reference statements)
3
43
1
Order By: Relevance
“…In addition, the current study also confirmed the findings of previous studies which tDCS enhancement of the motor learning is polarity dependent Stagg et al, 2011). Anodal tDCS could increase the rate of motor sequence learning, while cathodal tDCS induces opposite effects Stagg et al, 2011;Orban de Xivry and Shadmehr, 2014).…”
Section: Burning Sensationsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the current study also confirmed the findings of previous studies which tDCS enhancement of the motor learning is polarity dependent Stagg et al, 2011). Anodal tDCS could increase the rate of motor sequence learning, while cathodal tDCS induces opposite effects Stagg et al, 2011;Orban de Xivry and Shadmehr, 2014).…”
Section: Burning Sensationsupporting
confidence: 93%
“…In line with this finding, Hess et al (1996) also reported that a decrease in activity of GABAergic system is required for long-term potentiation in the motor cortex (Hess et al, 1996). In addition, it seems that a-tDCS over both M1 and cerebellum increases firing rate of neurons and strengthen the newly formed associations among neurons which can affect neural networks and consolidation of sequence learning task (Nitsche et al, 2003;Orban de Xivry and Shadmehr, 2014). Bindman et al (1962) also indicated that excitability of neurons was increased during and for several hours after anodal polarization.…”
Section: Burning Sensationmentioning
confidence: 67%
See 1 more Smart Citation
“…Additionally, previous studies from our group using chronic inflammation and hyperalgesia induced by chronic restraint stress models (Spezia Adachi et al, 2012) showed an antinociceptive effect of cortical stimulation by tDCS. Beyond the analgesic effect, human studies with tDCS have shown effects on motor control, stress, and depression, which could justify our results (Gonçalves, 2012;Nitsche et al, 2009a;Orban de Xivry and Shadmehr, 2014).…”
Section: Discussionmentioning
confidence: 54%
“…Adaptation of highly-learned, target-directed pointing or shooting movements to environment perturbations has been regularly investigated (Orban de Xivry & Shadmehr, 2014).…”
Section: Motor Learningmentioning
confidence: 99%